The Effectiviness Of Developing Students' Vocabulary Through Watching Animation Movie - Wijaya, Putri Bernika; Sutopo, Anam (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
Movies have become one of the most effective learning media in learning English, especially in Indonesia. Watching animated films can enhance students' language knowledge, speaking proficiency, and listening comprehension. This study aims at the effectiveness of developing students’ vocabulary acquisition through watching animation movie The Monkey and The Crocodile. This research uses qualitative methods with a narrative research design. This research will explore how students develop knowledge acquisition through animated films. Therefore, researchers use narrative research methods. The source of this research is all grade seventh students at SMP 1 Siwalan in 2024/2025 academic year. The students consist of 15 male and 16 female. The data analysis was obtained by a Thematic Analysis. Braun and Clarke (2006) outlined a set of theme-building procedures for the social sciences, but thematic analysis remains a loosely defined practice with many varied applications across fields of study and a “range of theoretical and epistemological approaches,” such as case study and ethnography. Interview, observation, and documentation were used in collecting the data. The finding shows that a clear improvement in students' vocabulary skills, with the average score increasing to 85.43, which is considered very good. This increase in score indicates that the use of animated films not only helps students master new vocabulary more easily, but also increases their confidence in using the vocabulary in communication. In addition, students also appear more enthusiastic and active in asking questions, discussing, and using the vocabulary they learned during the lesson